Job satisfaction of practice assistants in general practice in Germany: an observational study - Götz, Katja; Campbell, Stephen; Broge, Björn; Brodowski, Marc; Steinhäuser, Jost; Wensing, Michel; Szecsenyi, Joachim (Family practice, 2013)
Job satisfaction of practice staff is important for optimal health care delivery and for minimizing the turnover of non-medical professions.To document the job satisfaction of practice assistants in German general practice and to explore associations between job satisfaction, staff characteristics and culture in general practice organizations.The study was based on data from the European Practice Assessment accreditation scheme for general practices and used an observational design. The study population consisted of 1158 practice assistants from 345 general practices across Germany. Job satisfaction was measured with the 10-item Warr-Cook-Wall questionnaire. Organizational culture was evaluated with four items. A linear regression analysis was performed in which each of the job satisfaction items was handled as dependent variable.Out of 1716 staff member questionnaires handed out to practice assistants, 1158 questionnaires were completed (response rate: 67.5%). Practice assistants were most satisfied with their colleagues and least satisfied with their income. Higher job satisfaction was associated with issues of organizational culture, particularly a good working atmosphere, opportunities to suggest and influence areas for improvement and clear responsibilities within the practice team.Prioritizing initiatives to maintain high levels of, or to improve the job satisfaction of practice assistants, is important for recruitment and retention. It will also help to improve working conditions for both practice assistants and GPs and create an environment to provide better quality care.
Gesehen am 11.02.2020